Gestión financiera del rubro cuentas por cobrar de la empresa industria de fideos Pazmiño en los periodos 2019 – 2020 - León Tovar, Karla Liseth (2022)
Proper management of accounts receivable is essential for the proper development of companies engaged in various economic activities, since the proper management of the portfolio will contribute to the fulfillment of short-term obligations, in addition to generating greater profitability. The research called Financial Management of the accounts receivable item of the Pazmiño Noodle Industry Company in the periods 2019 - 2020, aims to study the various problems presented in the entity concerning the item of accounts receivable and the maturity of the portfolio, factors of great importance. for the operation of the organization, whose main activity is the production of Noelia noodles, defining as its main objective the examination of the accounts receivable item and the collection management applied by the Industrial Fideera Pazmiño, in order to achieve an efficient collection optimizing the process implemented in the collections area, achieve efficient management of production implements, through effective control that enables the maintenance of an acceptable stock in inventories. For which a non-experimental type investigation is used with a mixed approach, applying analytical and descriptive methods, which will allow an exhaustive analysis of the financial statements of the factory in the same way, an interview will be carried out with the person in charge of the collection department with the purpose of identify existing shortcomings, as well as possible improvements that could be implemented to increase productivity and therefore profitability through increased income.